THE EFFECT OF ELECTRONIC MONEY USE AND LIFESTYLE ON THE CONSUMPTIVE BEHAVIOR OF ECONOMICS EDUCATION STUDENTS, INTAKE 2022-2024, HKBP NOMMENSEN UNIVERSITY, PEMATANGSIANTAR - May Afriyanti Sinaga; Benjamin Albert Simamora; Susy Alestriani Sibagariang (RADJA PUBLIKA, 2025)
This study aims to determine the effect of electronic money use and lifestyle on the consumptive behavior of Economics Education Students, Intake 2022-2024, HKBP Nommensen University, Pematangsiantar. This study used a descriptive quantitative research method. Based on partial hypothesis testing, the results showed that electronic money had a positive and significant effect on consumptive behavior, as indicated by the calculated Tvalue (2.622) > Ttable (1.671), and lifestyle had no positive and significant effect on consumptive behavior, as indicated by the calculated Tvalue (1.265) < Ttable (1.671). Meanwhile, simultaneous hypothesis testing revealed that electronic money and lifestyle have a positive and significant effect on consumer behavior, as indicated by the calculated Fvalue (4.154) > Ftable (3.145). The coefficient of determination test yielded an R-square value of 0.120, indicating that 12% of the variables in electronic money and lifestyle influence the consumer behavior of Economics Education students in the 2022-2024 intake of HKBP Nommensen University, Pematangsiantar. The remaining 80% is attributed to other variables not examined in this study.